When digital government matters for tourism: a stakeholder analysis - Kalbaska, Nadzeya (2017)
Despite the importance of governance processes for destination management and the impact of digital technology on such processes, surprisingly little academic research has explored the use of digital technology to transform public governance in the tourism sector. This conceptual paper fills this gap by conducting a digital government stakeholder analysis for the tourism sector using the digital government evolution model as its theoretical foundation. The analysis identifies six relevant stakeholder groups: governments, businesses, non-profits, citizens, visitors and employees. It examines six types of technology-enabled interactions between government and other stakeholders: government-to-government, government-to-business, government-to-non-profit, government-to-citizen, government-to-visitor and government-to-employee. These interactions are illustrated with real-life examples. The analysis contributes to identifying pressures on tourism authorities and determining how the authorities respond to such pressures, how they innovate their operations and policies with digital technologies, and how these innovations are institutionalized over time. The results contribute to building the theoretical foundations for sector-specific digital government and enable strategic discussion on the use of commercially viable and socially responsible digital innovation to advance the tourism sector.